Edukasi Finansial Generasi Z: Dari Pola Hidup Instan Menuju Masa Depan Berkelanjutan : Studi Kegiatan Kuliah Kerja Nyata di Desa Manikmaraja, Kabupaten Simalungun - Nazwa Sabina Nasution; Riska Sri Lestari; Lira Amelia; Zulkarnain Abdurrahman (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2026)
Generation Z is known as a generation that is highly connected to technology and tends to adopt a fast-paced lifestyle. These habits often lead to a consumptive lifestyle and poor long-term financial planning. To respond to this phenomenon, students through the Community Service Program (KKN) conducted financial education activities in Manikmaraja Village, Simalungun Regency. This activity involved YPI Dharma Budi High School students and the local youth community. The program used a descriptive qualitative approach, which included outreach, workshops, interactive discussions, and evaluations. The results of this activity showed an increase in participants' knowledge of financial literacy, appreciation of the importance of saving, and ability to prepare a basic budget. This program demonstrated that incorporating financial literacy into daily life planning can help individuals become more independent and aware of the importance of financial management. Overall, this activity successfully increased financial literacy among the younger generation in the village.